Utilizing botley robotics to facilitate the development of computational thinking skills in children with visual impairment - Pamungkas, Mey Tias Andry; Budiyanto, Cucuk Wawan; Suharno, Suharno (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Computational thinking (CT) skills have become increasingly vital in the digital age, particularly for children with visual impairments who often encounter challenges in accessing technological education. This study aims to explore the use of Botley Robotics as a tool to facilitate CT skills and its application in the learning context. Employing qualitative methods through observations, questionnaires, and interviews, this research involved two students with visual impairments from a special needs school in Indonesia, selected through purposive sampling. Botley, a screenless robot, served as the primary learning medium. The data collected were analyzed using the CT framework from Brennan and Resnick, which encompasses three main dimensions: computational concepts, practices, and perspectives. The findings indicate that Botley Robotics effectively facilitates CT skills in students, particularly in areas such as debugging, programming, and logical reasoning. Despite their visual limitations, the students demonstrated the ability to program the robot and understand complex statements and logical operators. The conclusions drawn from this research suggest that Botley can serve as a valuable tool for fostering CT skills among students with visual impairments by integrating concepts from the Brennan & Resnick framework. The tactile and auditory feedback provided by Botley enables children to develop problem-solving and logical thinking skills through direct interaction. This study highlights the significance of incorporating robotic technology into inclusive education and demonstrates the substantial potential of Botley Robotics to enhance access to and the quality of education for children with visual impairments. Therefore, it is recommended that this technology be implemented more broadly within the context of inclusive education.